Biodegradable polyester/modified mesoporous silica composites for effective bone repair with self‐reinforced properties. (20th February 2019) - Wang, Jielin; Yu, Jianshu; Yan, Yinan; Yang, Dicheng; Wang, Ping; Xu, Yan; Zhu, Jun; Xu, Guohua; He, Dannong; Huang, Gang
Abstract : A series novel composites based on poly(L ‐lactide) (PLLA) oligomer modified mesoporous silica (MCM41) homogeneous dispersed into poly(L ‐lactide‐ co ‐trimethylene carbonate‐ co ‐glycolide) (PLTG) terpolymer has been successfully prepared. The structure of PLTG terpolymer was characterized by 1 H NMR. The structure and properties of modified and unmodified MCM41 were attested by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analyzer (TGA), X‐ray diffraction (XRD), N2 adsorption–desorption, scanning electron microscope (SEM), and transmission electron microscope (TEM), which demonstrated that the MCM41 was successfully grafted by the PLLA oligomer. The effect of different concentration of modified MCM41 in PLTG matrix on thermal properties, mechanical properties, and hydrophilicity was investigated by TGA, differential scanning calorimetry (DSC), mechanical testing, contact angle measurement, and SEM. The results of mechanical tests showed that 5 wt% of modified MCM41 nanoparticles gave rise to optimal reinforcing effect. The tensile strength, Young's modulus, and elongation at break of the PLTG/PLLA‐MCM41 (5%) composites were 33.2 Mpa, 1.58 Gpa, and 268.7%, respectively, which were all higher than the PLTG/MCM41 (5%) composites and pristine PLTG matrix, which were due to good interfacial adhesion between the PLTG matrix and MCM41 nanoparticles. TGA and DSC have shown that 5% modified MCM41 in the PLTG increased the temperature of composite degradation and T g . Water contact angle measurement showed the hydrophilicity of the composites increases with the increase of modified MCM41 content. The live/dead assay showed that the modified MCM41 existing on the PLTG matrix presents very excellent cytocompatibility. Therefore, the novel composite material represents promising way for bone tissue engineering application.